Suppressive activity of volatile fatty acids and aromatic carboxylic acids on the germination of Monochoria vaginalis - Junko Tazawa (Taylor & Francis Group, 2021)
Rice bran application is practically used by Japanese organic rice farmers as a common measure in controlling Monochoria vaginalis, a known weed in organic rice production. To elucidate the inhibitory mechanisms of rice bran application on M. vaginalis germination, we focused on volatile fatty acids (VFAs) and aromatic carboxylic acids (ACAs) as organic acids produced through rice bran decomposition in the soil, which can possibly suppress M. vaginalis germination. Both solo solutions of 1 mM VFAs (propionic or isobutyric acid) and 0.2 mM ACAs (3-phenylpropionic or 4-phenylbutyric acid) exhibited M. vaginalis germination suppression, especially at pH 4.6, the lowest pH tested. In the 0.5–3 mM VFA solutions at pH 4.6, germination was strongly suppressed in the order of isobutyric > propionic > butyric > acetic acid. With the 0.05–0.2 mM ACA solutions at pH 4.6, the germination was strongly suppressed in the order of 3-phenylpropionic > 4-phenylbutyric > 2-phenylpropionic acid. Benzoic acid did not exhibit significant germination suppression. The solutions of 0.5 mM VFAs and 0.05 mM ACAs exhibited no suppression when applied separately; however, the certain mixture of a VFA and an ACA at the aforementioned concentration, for example, 0.5 mM isobutyric acid and 0.05 mM 3-phenylpropionic acid, exhibited significant germination suppression. These results showed the several combinations of VFAs and ACAs at even non-effective concentrations synergistically suppressed M. vaginalis germination. Abbreviations:2PPA: 2-phenylpropionic acid; 3PPA: 3-phenylpropionic acid; 4PBA: 4-phenylbutyric acid; ACA: aromatic carboxylic acid; EC: electrical conductivity; M. vaginalis: Monochoria vaginalis; VFA: volatile fatty acid